Penggunaan tepung daun kelor (Moringa oleifera) berbeda komposisi dalam formulasi pakan bagi pertumbuhan ikan nila (Oreochromis niloticus) - Pamula, Doni F.; Lumenta, Cyska; Monijung, Revol D.; Mokolensang, Jeffrie F.; Pangkey, Henneke; Sambali, Hariyani (Universitas Sam Ratulangi, 2024)
Several previous studies regarding the use of Moringa leaf flour on fish had been carried out fish consumption including catfish, tilapia, and gourami. The objectives of this research were to determine the effect of substitution of Moringa leaf flour at different doses in feed formulation on the relative growth of tilapia and determine which treatment had the highest feed efficiency value. The results showed relative weight growth value for tilapia were obtained in treatment C (83.82%), daily growth (C) 2.03%, food conversion ratio (FCR) 1.29, and Feed Efficiency 77.01%. Keywords: relative growth, daily growth, feed conversion ratio, feed efficiency value.